Macro level measuring of organization legitimacy: Its implication for open innovation - Adrián López-Balboa; Alicia Blanco-González; Francisco Díez-Martín; Camilo Prado-Román (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Although the field of organizational legitimacy is undergoing great advances, academics are still facing the challenge of its measurement. Currently, academics are focusing on improving and homogenizing legitimacy measurement systems at the micro level. However, measuring legitimacy at the macro level has not evolved according to the needs and possibilities provided by new technologies. This research aims to develop a new methodology to measure organizational legitimacy at the macro level, capable of processing large amounts of information. To this end, an analysis of the news content of the 50 companies that make up the EuroStoxx50 has been conducted for a full year. By doing so, we make three key contributions to managing organizational legitimacy. First, we provide a more complete and reliable measurement of organizational legitimacy thanks to mass information processing techniques, providing a technology-based solution to the obsolescence problem of legitimacy evaluation models at the macro level. Second, we provide empirical evidence of the relationship between legitimacy and organizational success based on the analysis of mass information. Third, we show evidence that a bias is introduced in the measurement of legitimacy due to the use of different sources for this purpose.
Keywords: 650; legitimacy; media; news aggregator